Improving teachers' self-efficacy in applying teaching and learning strategies and classroom management to students with special education needs in Hong Kong. (August 2017) - Chao, Chih Nuo Grace; Chow, Wing Sze, Emily; Forlin, Chris; Ho, Fuk Chuen
Abstract: This study examines the impact of a revised one-week training course on teacher self-efficacy in terms of improving teaching and learning strategies and classroom management to support students with special educational needs (SEN) in ordinary schools in Hong Kong. Various teacher-related variables (i.e., level of prior training in special education, confidence in teaching students with SEN, knowledge of legislation and policies, years of teaching, teaching experience with students with SEN, gender, and school type) are analyzed among 347 regular primary and secondary teachers. Teacher confidence and school type are determined to be significant predictors for the self-efficacy of teachers in inclusive education. Highlights: The training course improved teachers' self-efficacy for supporting SEN students. Confidence was a significant predictor of self-efficacy in classroom management. Confidence and school were significant predictors for teacher self-efficacy.